ASSESSMENT OF VAM SPORE DENSITY AND ROOT INFECTION FROM ALLUVIAL SOIL OF EASTERN PART OF RANIGANJ COALFIELD AREAS - SANJOY KUMAR,; S. CHAUDHURI,; S. K. MAITI, (The Bioscan, 2011)
The indices of occurrence of VAM are widespread in natural vegetation, but intensity of distribution and root infection varies among types of species, nature of edaphic factors of soil. In this study, we observed that the VAM spore density and their colonization also positively correlated with depth of soil profile (p<0.05); available nitrogen, organic matter and available phosphorous. The most commonly genus of VAM spores found in the study area are Glomus, Gigaspora, Acaulospora, Enterophospora and Sclerocystis. Glomus and their size frequency distribution range from 50-75 μm and 75-100 μm. The highest number of VAM spore density/5 g of soil were found as 360.0±12.5 and for VAM spore density/100g of soil were found as 702.0 ± 23.87 in mine 3. The highest number of VAM spore density was reported under the Acacia auriculoloformis. The percentage of root colonisation observed in seven native species are; Dalbergia sissoo (91%), followed by Prosopis juliflora (84%), A. auriculiformis (79%) and A. scholaris (64%), Polyalthia longifolia (58%), Cassia seamea (31%), and Azardirachta indica (21%). The studies revealed that vesicular-arbuscular mycorrhiza is essential to assess the self-sustaining ecosystem of soil quality and which should be used for amendments in mine degraded soils for reclamation and restoration process.